Meta-Analysis of Daoyin Therapy on Therapeutic Effect and Quality of Life in Patients with Stable Angina Pectoris - QIAO Meng; WANG Zhifei; TAN Chaoren; DAI Jingang (康复学报)
ObjectiveTo evaluate the therapeutic effect and quality of life of Daoyin therapy in the treatment of stable angina pectoris of coronary heart disease.MethodsEight databases, including CNKI, VIP, Wanfang, SinoMed, PubMed, Cochrane Library, Embase, and Web of Science were searched through the computer retrieval system, and the RCTs of Daoyin therapy for stable angina pectoris were screened. The retrieval time was from inception to December 2021.The risk of bias assessment tool provided by the Cochrane Reviewers Handbook 5.1 was used to assess the quality of the literature, and the RevMan 5.3 software (provided by the Cochrane Collaboration) was used to perform a meta-analysis. Primary outcomes included the number of angina attacks, the angina duration and Seattle angina questionnaire (SAQ) scores. Secondary outcomes included Self-Rating Anxiety Scale (SAS) scores, Self-Rating Depression Scale (SDS) scores, 6-minutes walk test (6MWT) and Metabolic Equivalents (METs）. Continuous variables were expressed by Mean Difference (MD) and 95% confidence interval (CI). If the included studies were homogeneous (P>0.1, I2≤50%), a fixed effects model would be used; if the included studies were heterogeneous (P≤0.1, I2>50%), a random-effects model would be used.ResultsA total of 15 RCTs were included, involving 1 261 cases, with 631 in the Daoyin group and 630 in the control group. The overall quality of the included studies was not high. Meta-analysis showed that compared with the control group, Daoyin therapy can significantly reduce the number of angina pectoris attacks [MD=-1.70, 95%CI (-2.07, -1.34), P<0.000 01], shorten the duration of angina pectoris [MD=-1.17, 95%CI (-1.38, -0.96), P<0.000 01], reduce SAS scores [MD=-4.71, 95%CI (-7.12, -2.31), P=0.000 1] and SDS scores [MD=-3.91, 95%CI (-5.75, -2.07), P<0.000 1], and improve METs [MD=1.20, 95%CI (0.39, 2.01), P=0.004] and SAQ scores [MD=7.62, 95%CI (5.97, 9.27), P<0.000 01]; Taijiquan [MD=39.52, 95%CI (19.30, 59.74), P=0.000 1] and Shaolin Neigong (P<0.000 1) can improve 6MWT, while Baduanjin [MD=1.39, 95%CI (-9.13, 11.92), P=0.80] and Yixincao (P=0.30) have no statistical difference in improving 6MWT.ConclusionDaoyin therapy is effective to treat patients with stable angina pectoris of coronary heart disease by improving clinical efficacy, alleviating depression and anxiety symptoms and improving quality of life when applied alone or as an add-on measure to the conventional therapy/exercise.